The relationship between collaboration in learning, quantity and timing of feedback, and self-efficacy of students in higher education / Chan Yuen Fook … [et al.] - Chan, Yuen Fook; Kaur Sidhu, Gurnam; Narasuman, Suthagar; Lee, Lai Fong; Yap, Bee Wah (UiTM Press, 2016)
The purpose of this study was to identify the effect of collaboration in learning, and the quantity and timing of feedback towards the enhancement of self-efficacy among students in a public university in Malaysia. Data was collected using a survey questionnaire. The questionnaire was distributed to a total of 500 randomly selected tertiary students. A total of 475 questionnaires were returned and used for analysis. Data was analysed with both descriptive and inferential st atistics. The findings revealed that most of the students collaborate with peers in their learning. Feedback that was identified has a positive and significant relationship with student selfefficacy. A moderate, positive and significant correlation has been identified between collaboration in learning, quantity and timing of feedback and selfefficacy among the students in a public university. However, collaboration in learning and quantity and timing of feedback only induced a low effect size on self-efficacy.